Southern Rhodesia’s relationship with South Africa, 1923-1953 - Mlombo, Abraham (University of the Free State, 2017)
This thesis is a historical examination of Southern Rhodesia-South Africa relations from 1923 to 1953. Although some historians have paid attention to this “special relationship”, this thesis argues that the relationship is far more intricate and complex than the existing historiography allows for. In particular, it highlights the complexity of the ties between the two countries by studying the political relations, economic links and social and cultural ties between the two. By 1923, Southern Rhodesia had attained responsible government, in the process rejecting union with South Africa. Multiple factors contributed to this development, most notably anti-Afrikaner sentiments. It is this antagonistic, ambiguous relationship that this thesis significantly details and analyses. The thesis is organised chronologically, and discusses the multi-faceted nature of relations between Southern Rhodesia and South Africa. As is argued, economic ties (in particular customs and trade agreements) were the cornerstone of relations. Economic ties were fluid; they were characterised by close ties as well as friction between the two countries. Changes in the nature of economic relations influenced other aspects of Southern Rhodesia-South Africa relations. In addition, this thesis pays close attention to relations during the Second World War, whilst also examining social and cultural ties such as the role of sport and migration. Archival sources in South Africa, Zimbabwe and Britain were used for this thesis. These sources were supplemented by South African and Zimbabwean newspapers and periodicals. Situated within the broader framework of Southern African history, the thesis provides a lens through which to study the economic, political and social forces that characterised the colonial period in the region. The thesis also contributes to area studies – it shows that, by studying Southern Rhodesia-South Africa relations, it becomes evident that countries and settler societies bound by geographical contiguity are not monolithic and do not necessarily maintain harmonious relations. The importance of the thesis from an imperial perspective is that it interweaves economic, political and social developments to provide a multifaceted analysis of British relations with Southern Africa.

Hierdie proefskrif is ŉ historiese ondersoek na betrekkinge tussen Suidelike Rhodesië en Suid-Afrika van 1923 tot 1953. Hoewel sommige geskiedkundiges reeds aandag gegee het aan hierdie “spesiale verhouding”, argumenteer hierdie proefskrif dat die verhouding baie meer verwikkeld en kompleks is as wat die bestaande geskiedskrywing aandui. Hierdie proefskrif belig veral die kompleksiteit van die bande tussen die twee lande deur die politieke verhoudinge, ekonomiese betrekkinge en sosiale en kulturele bande tussen hulle te bestudeer. Teen 1923 het Suidelike Rhodesië verantwoordelike regering bereik, en in die proses is samesmelting met Suid-Afrika verwerp. Veelvuldige faktore (in die besonder anti-Afrikanergevoelens) het bygedra tot hierdie verwikkeling. Dit is hierdie antagonistiese, meerduidige relasie wat op beduidende wyse in besonderhede in die proefskrif uiteengesit en ontleed word. Die proefskrif is chronologies gestruktureer en bespreek die veelfasettige aard van verhoudinge tussen Suidelike Rhodesië en Suid-Afrika. Soos wat aangevoer word, was ekonomiese bande (veral doeane - en handelsooreenkomste) die hoeksteen van verhoudinge. Ekonomiese bande was vloeibaar; hulle is gekenmerk deur noue betrekkinge asook wrywing tussen die twee lande. Veranderinge in die aard van ekonomiese relasies het ander aspekte van verhoudinge tussen Suidelike Rhodesië en Suid-Afrika beïnvloed. Die proefskrif gee ook nougesette aandag aan verhoudinge gedurende die Tweede Wêreldoorlog, terwyl sosiale en kulturele bande soos die rol van sport en migrasie ook ondersoek word. Argiefbronne in Suid-Afrika, Zimbabwe en Brittanje is vir hierdie proefskrif gebruik. Die bronne is aangevul deur Suid-Afrikaanse en Zimbabwiese koerante en tydskrifte. Binne die breër raamwerk van Suider-Afrikaanse geskiedenis voorsien die proefskrif ŉ lens waardeur die ekonomiese, politieke en sosiale kragte wat kenmerkend was van die koloniale tydperk in die gebied, bestudeer kan word. Die proefskrif dra ook by tot gebiedstudies deur te toon dat dit uit die bestudering van relasies tussen Suidelike Rhodesië en Suid-Afrika blyk dat lande en setlaarsgemeenskappe wat deur geografiese aangrensing beperk word, nie monolities is nie en nie noodwendig harmonieuse verhoudinge handhaaf nie. Vanuit ŉ imperiale perspektief gesien, is hierdie proefskrif belangrik omdat dit ekonomiese, politieke en sosiale verwikkelinge verweef om ŉ veelfasettige analise van Britse verhoudinge met Suid-Afrika te verskaf.
Thesis (Ph.D. (Centre for Africa Studies))--University of the Free State, 2017
Keywords: Responsible government; Customs agreements; Federation; Afrikaner nationalism; Immigration; South Africa; Southern Rhodesia; Settlers